EKSPLORASI ETNOMATEMATIKA PADA BATIK GAJAH MADA MOTIF SEKAR JAGAD TULUNGAGUNG - Afifah, Dian Septi Nur; Putri, Ika Mariana; Listiawan, Tomi (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
Ethnomathematics is mathematics that found in the culture. The purpose of this research is to explore mathematical concepts in Gajah Mada Batik’s Motif Sekar Jagad Tulungagung. The research method used is qualitative method with an ethnographic approach. Data collection techniques used library studies, interview, and documentation. Data analysis techniques used data reduction, data presentation, conclusion. Checking the data validity is done by extending the observation, increasing perseverance, using reference material, member check. The result of this research, in Gajah Mada batik’s there are mathematical concepts in the form of two-dimensional figure, transformation geometry, angles, and line. The two-dimensional figure found in this batik is parallelogram, ellipse, rhombus. The transformation geometry that found in this batik is reflection. While the angles and line that found in this batik are obtuse, parallel line, opposite angle, upfront angle, opposite interior angle, opposite outside angle, upfront interior angle, upfront outside angle.